(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2015)
This article discusses the different aspects that affect the international mobility of engineering professionals from the field of professionalism, institutionalism and relationships between these theories presented. The importance of the engineering profession as high impact activity to society, in terms of good professional practice, competencies and skills of professionals, regulators professions, the importance of professional certification related to compliance with requirements regulators themselves